Investimentos socioambientais para posicionamento de marca: um estudo sobre imagem organizacional - Castro, Aline Eggres de (2011)
This study aims to investigate how the Social and Environmental Investments and other actions of Corporate Social Responsability of the companies impact on organizational image of them before their customers. The theme is justified by the need to verify that such actions bring effective results in the quest for improved organizational image. For a better understanding of the topic, literature search was conducted on the topics of organizational image, Social Responsibility, Institutional Marketing and Communications. The company Natura Cosmetics SA was chosen as an object of study due to its strong performance in the social, environmental and cultural areas in the country. The actions carried out by the company were described in this study through a literature search conducted on the company s publications about the subject and segmented into three categories: Ecologic Marketing, Cultural Marketing, and Social Marketing. To achieve the objectives of the study, a survey was conducted with the consultants (sellers of products). This public was chosen because they are considered to be the first consumers of Natura s products. The survey was conducted through a questionnaire, developed from a hypothetical model of research adapted from Gonçalves Filho et al (2009). The results indicated that the activities better known by the respondents are the ones about ecology, which are directly related to the identity linked to natural products that do not harm the environment that the company transmits (therefore, they are well communicated) and the program "Believe to See, "which has a line of products aimed at raising funds to it, so the consultants are in frequent contact. The respondents were asked about their opinion on the investments and 99.2% have positive view, with only one respondent has indifferent vision. Moreover, 80% of respondents said that the realization of these actions positively affect their opinion on the company. The focus of the study, however, was to investigate the impact of specific actions, whereas other studies have already shown the impact of Social Responsibility actions in general. Thus, the consultants were asked about what actions impacted the most their opinion about the company. The results indicate that the activities that are better communicated are also those that most affect the opinion, especially those related to ecology and society. The actions related to culture, however, even when properly communicated don t have relevant return on image, compared to the returns of other kind of actions. The results, therefore, allowed to accept two hypotheses made (related to ecology and society) and refute one of the hypotheses (related to cultural activities).